Islamic Legal Justice and The Challenges of International Trade Liberalization - Roy, Royani; Mahmud, Mahmud; Rosadi, Aden; Setiawan, Iwan (Amwaluna: Jurnal Ekonomi dan Keuangan Syariah, 2025)
International trade liberalization creates significant structural imbalances in Muslim-majority countries, primarily evident in the unequal distribution of trade benefits and the exploitation of resources. The key problem is the lack of an evaluation framework that combines Islamic justice principles (‘adl) with modern trade data to measure how liberalization policies impact Muslim communities. This study examines the compatibility of international trade liberalization with Islamic economic values and develops a practical evaluation model for the design of trade policies in Muslim countries. Unlike earlier studies, it creates a new analytical framework that integrates the three dimensions of justice in Islam (distributive, procedural, and corrective justice) with current trade indicators, using a qualitative approach and systematic literature review, supplemented with contemporary Islamic interpretations of trade in the Quran and hadith. The research introduces the "Islamic Just Trade Model," offering a fresh perspective on relevant Quranic verses (Al-Baqarah: 275 and An-Nisa: 29) for today’s global trade. Findings indicate that while Islam supports international trade for economic growth, uncontrolled liberalization conflicts with core Islamic values of justice, equality, and social welfare. The study identifies five practical indicators to assess fairness in international trade according to Islamic principles: Bilateral Benefit Balance Index, Strategic Sector Protection Index, Trade Profit Distribution Index, Environmental Sustainability Index, and Social Welfare Index, providing Muslim countries with policy tools to design trade strategies in line with Sharia and address structural inequalities from global trade liberalization.